Self-concept and depression in undergraduate students at a private university - Bartra Alegría, Andrés Fernando (2016)
The aim of this study was to assess the relationship between self-concept and depression in undergraduate students of a private university of Tarap-oto. The sample consisted of 465 students, both sexes between 16 and 35 years. A non-experimental descriptive correlational design was used. Instruments: AF5 Self-Concept Scale Garcia and Musitu and consists of 30 items and the Beck Depression Inventory Adapted consisting of 21 items. The psychometric properties of the instruments indicated that they are valid and reliable. The results show that there is a highly significant inverse relationship between self-concept and depression in college students (r = -.462 ** p <0.01) indicating that major depression to low self-concept.